Inclusion of biopiperine in the kappa-carrageenan complex might improve its bioaccessibility and in vivo anti-inflammatory activity in edema-induced Wistar rats - Nela Simanjuntak, Jutti Levita, Anas Subarnas (Journal of Applied Pharmaceutical Science, 2020)
Piper nigrum has been used in Indonesian traditional medicine to alleviate pain. Piperine, a nitrogenous substance isolated from the plant, has been reported for its anti-inflammatory activity. However, this compound is slightly soluble in water, which impacts its bioaccessibility. A recent study reported that a co-ground mixture of piperine and β-cyclodextrin revealed a significant increase of dissolved piperine at 15 minutes of dissolution test compared to that of pure piperine. This work was aimed to study the bioaccessibility of the carrageenan-complexed piperine in Wistar rats and assayed its anti-inflammatory activity on the edema-induced paw of the rats. Both isolated (from P. nigrum) and synthetic (TCI, Tokyo Chemical Industry) piperines were used as the standards for the bioaccessibility assay, whereas acetosal was the standard drug for the anti-inflammatory activity study. The carrageenan-complexed piperine revealed a better bioaccessibility (Cmax = 0.34 μg/ml; Tmax at 30 minutes) than that of the isolated piperine (Cmax = 0.12 μg/ml, Tmax at 60 minutes), whereas the synthetic piperine showed the best absorption (Cmax = 0.48 μg/ml, Tmax at 30 minutes). The anti-inflammatory activity of carrageenan-complexed piperine at a dose of 393 mg/kg body weight (BW) (contains 100 mg of piperine) equals to the acetosal dose of 45 mg/kg BW. Thus, the inclusion of biopiperine in the carrageenan complex might improve its bioaccessibility and in vivo anti-inflammatory activity in Wistar rats.
Keywords: Anti-inflammatory, Carrageenan, Piperaceae, piperine.